Inhibitory Activity of Myrtus communis Oil on Some Clinically Isolated Oral Pathogens - Fani, Mohammad Mehdi (Med Princ Pract, 2014)
OBJECTIVES: To determine the antimicrobial activities of Myrtus communis oil (MCO) on some oral pathogens. MATERIAL AND METHODS: Thirty strains of Streptococcus mutans, Aggregatibacter actinomycetemcomitans, Porphyromonas gingivalis and 20 strains of Streptococcus pyogenes and Candida albicans isolated from patients with dental caries, periodontal diseases, pharyngitis and oral lesions associated with artificial dentures were used for the antimicrobial activity of MCO. The oil was prepared by hydrodistillation procedures using a Clevenger apparatus. Agar disk diffusion and broth microdilution methods were performed on various concentrations of MCO (3.9–1,000 µg/ml) using all the pathogens isolated. RESULTS: All isolates were sensitive to MCO at 125–1,000 µg/ml by agar disk diffusion producing inhibition zones of 8.1–41.25 mm in diameter. All of the S. pyogenes, S. mutans and C. albicans strains were sensitive to 62.5 µg/ml while 70% (21/30) of A. actinomycetemcomitans and 66.6% (20/30) of P. gingivalis were resistant to these concentrations. All S. pyogenes and S. mutans strains were sensitive to 31.25 µg/ml. All S. pyogenes strains were sensitive to 15.6 and 7.8 µg/ml of MCO. None of the clinical isolates in this study were sensitive to 3.9 µg/ml or to a lower concentration of oil. The minimum inhibitory concentrations of MCO for S. pyogenes, S. mutans, C. albicans, A. actinomycetemcomitans and P. gingivalis were 29.68 ± 4.8, 31.25 ± 0, 46.9 ± 16, 62.5 ± 0 and 62.5 ± 0 µg/ml, respectively. CONCLUSIONS: Data obtained in this study revealed a strong antimicrobial activity of MCO on the tested oral pathogens, and MCO could therefore be useful in the prevention of the related oral infections.